RANCANGAN APLIKASI SPK PENENTUAN WALI KELAS BERDASARKAN PRESTASI GURU DENGAN METODE AHP PADA SMK JAKARTA BARAT 1 - Sundari, Yola; shevti Arbekti Arman; Diana Yusuf (Jurnal Sistem Informasi (JUSIN), 2024)
A decision support system (DSS) is the definition of a procedural model of data processing and assisting management in making decisions. Computer-based decision support systems can improve decision-making ability to solve problems that appear structured or unstructured. The Analytical Hierarchy Process (AHP) method can be used to solve the DSS problem. This method is one of the most sought-after optimal solutions among several other decision support system method options. The research was conducted at SMKN 1 West Jakarta which aimed to assist the school in selecting homeroom teachers based on the effectiveness of teachers in the learning process to students. The creation of this application is done through data collection, system design, system analysis and database design. The creation of this application program is developed using PHP, the database is MySQL. In running this application, input or alternative information is needed, namely the names of teachers, and the assessment criteria are professional values, pedagogic values, personality values, and social values. The process requirements needed are alternative data entry process, teacher data entry process and also criteria data. The result is a teacher report that is expected to help the principal to determine homeroom based on teacher achievement scores.